Personality, Plasticity and Predictability in Wild White-Footed Mice - Kermany, Natalie (Université d'Ottawa / University of Ottawa, 2020)
Recently, there has been an explosion of studies focusing on animal “personality”, defined as consistent individual differences in behaviour. Researchers within this field commonly partition phenotypic variation in behavioural traits at the among- and within-individual levels, because significant among-individual variation implies that a behaviour is repeatable and thus can be subject to selection. It is well known that individuals can not only differ in their mean-level behavioural expression, but also in how their phenotype varies over time, known as temporal plasticity. However, another important yet largely overlooked aspect of behavioural variation is that some individuals are consistently more “unpredictable” than others. This level of variance corresponds to (unexplained) variation among successive measurements on a given individual. Personality and behavioural plasticity have both been studied in many different contexts, however research regarding the possible correlations between these two traits and unpredictability is lacking. Here, I repeatedly assayed locomotor activity in wild white-footed mice (Peromyscus leucopus) exposed to a 10-min novel environment test, to determine whether their behavioural reaction norms exhibited consistent among-individual differences in intercept (personality), slope (plasticity), and variance (unpredictability). Using a doubly hierarchical generalized linear mixed model, I found that both the intercept and slope of the temporal reaction norms were significantly repeatable (Rint= 0.39, Rslp= 0.23) and negatively correlated (r=-0.51). Moreover, unpredictability was found to be significantly repeatable (Rsd= 0.20), positively correlated with intercept (r=0.92), and negatively correlated with slope (r=-0.51). To the extent that these correlations reflect the underlying quantitative genetic architecture of behaviour, my results suggest the presence of constraints on the evolution of behaviour across multiple levels of variation.
Keywords: Personality; Plasticity; Predictability; Reaction Norm; Mice; Exploration